Chemical constituents of Zizyphus sativa Gaertn fruits. Part II - Triterpenoid acid - Hoang Anh, Nguyen Thi; Sung, Tran Van; Wessjohann, L. (Vietnam Journal of Chemistry, 2014)
Three terpenoid acids have been isolated from an ethyl acetate extract of Z. sativa fruits. Their structures were established as betulinic, oleanolic and maslinic acids by means of MS, NMR spectroscopic data and by comparison with reported data.